Congenital rubella syndrome: A brief review of public health perspectives - Ashlesha Kaushik; Sanjay Verma; Praveen Kumar (Wolters Kluwer Medknow Publications, 2018)
Congenital rubella syndrome (CRS) is one of the most devastating congenital infections and yet the only one which is vaccine preventable and is a public health challenge for clinicians and policymakers across the developing world including India. The clinical manifestations of CRS include growth retardation, cardiac defects, cataracts, and hearing impairment. The World Health Organization (WHO) estimates that worldwide over 100,000 babies are born with CRS every year despite the availability of safe and inexpensive vaccines, thus highlighting the need for broader vaccination coverage programs. This article briefly reviews the importance of CRS, the proposed strategies for prevention by the WHO, and the "Rubella initiative" that Government of India is launching in view of the recognition of CRS as a significant problem in India.